2019
DOI: 10.1096/fj.201801256rr
|View full text |Cite
|
Sign up to set email alerts
|

TAZ stimulates liver regeneration through interleukin‐6–induced hepatocyte proliferation and inhibition of cell death after liver injury

Abstract: In response to liver injury, the liver undergoes a regeneration process to retain its mass and function. However, the regeneration mechanism has not been fully clarified. This study investigated the role of transcriptional coactivator with PDZ‐binding motif (TAZ), a Hippo‐signaling effector, in liver regeneration. We observed that TAZ stimulates liver regeneration after liver injury. After partial hepatectomy (PHx) or carbon tetrachloride damage, TAZ was required for liver regeneration to increase hepatic cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 52 publications
0
23
0
Order By: Relevance
“…YAP and TAZ regulate the expression of genes important for the control of cell proliferation and survival 28,30 . Active YAP appears to be important for the sustained expression of cell cycle genes in hepatocytes, 40 and genetic ablation of YAP and/or TAZ impairs hepatocyte proliferation during liver regeneration 25,41 . The findings of the present study suggest that sensory nerves are able to control YAP/TAZ‐mediated hepatocyte proliferation via the CGRP‐RAMP1 signaling pathway.…”
Section: Discussionmentioning
confidence: 54%
“…YAP and TAZ regulate the expression of genes important for the control of cell proliferation and survival 28,30 . Active YAP appears to be important for the sustained expression of cell cycle genes in hepatocytes, 40 and genetic ablation of YAP and/or TAZ impairs hepatocyte proliferation during liver regeneration 25,41 . The findings of the present study suggest that sensory nerves are able to control YAP/TAZ‐mediated hepatocyte proliferation via the CGRP‐RAMP1 signaling pathway.…”
Section: Discussionmentioning
confidence: 54%
“…However, several studies reported strong regeneration defects in Yap, Taz, or Yap/Taz mutant livers after partial hepatectomy or BDL. 2,7,18 These studies, however, deleted Yap and/or Taz from hepatoblasts using Alb-Cre or from adult hepatocytes and BECs by Mx1-Cre, and did not determine the specific requirements for Yap/Taz in hepatocytes vs BECs. Therefore, we conclude that Yap/Taz are largely dispensable in hepatocytes for the induction of the regeneration program and for regenerative proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…14,15 Conversely, liver-specific deletion of Yap (and Taz) reduced and/or delayed regenerative cell proliferation of hepatocytes after different types of liver damage, such as that caused by partial hepatectomy, toxic liver injury, and bile duct ligation (BDL). 2,[7][8][9][16][17][18] However, the severity of the observed regeneration defects was highly inconsistent between different studies, ranging from no obvious effects to delayed regeneration. These ambiguous results might be explained by the different knockout methods employed.…”
Section: Background and Aimsmentioning
confidence: 99%
“…Furthermore, studies demonstrated that TGF-β contributes to induction of apoptosis in hepatocytes as TGF-β-treated rat liver cells or human liver cell lines undergo apoptosis upon in vitro stimulation (26, 27, 38). IL-6 is known for its contribution to liver regeneration and is described to protect against liver damage (39). For example, IL-6 was shown to reduce acetaminophen (APAP)-induced liver injury in mice (2830).…”
Section: Discussionmentioning
confidence: 99%